Efficacy of prednisolone for children with acute bronchiolitis having family history of atopy: A randomized placebo-controlled trial (Northern International Medical College Journal, 2015)
Objective : To determine the efficacy of oral prednisolone among children with acute bronchiolitis who have associated family history of atopy.Materials and Methods : This randomized double blind placebo controlled trial was carried out in Dhaka Medical College Hospital during July08 to June10. A total of sixty patients (1-24 months) of acute bronchiolitis who had family history of atopy (e.g. allergic rhinitis, allergic conjunctivitis, asthma, eczema) were enrolled. After enrollment, allocation of either prednisolone or placebo to the study subjects were done randomly by lottery method and the researcher remained blind about the allocation. Finally 30 cases received prednisoloneorally at a dose of 2mg/kg/day 8 hourly for 3 consecutive days and 30 cases received placebo (made of flour). In addition, both the groups got same supportive measures. During intervention, study subjects were monitored by Modified Respiratory Distress Assessment Instrument (MRDAI) score twice daily for consecutive 3 days. Duration of oxygen therapy as well as length of hospital stay was also determined. Data were analyzed using appropriate statistical tests and a p value of